2020
DOI: 10.1097/ico.0000000000002534
|View full text |Cite
|
Sign up to set email alerts
|

Procedures, Visits, and Procedure Costs in the Management of Microbial Keratitis

Abstract: Purpose: To investigate the burden of procedures, visits, and procedure costs in the management of microbial keratitis (MK). Methods: Medical records of patients from an academic hospital outpatient facility between December 2013 and May 2018 were retrospectively reviewed. Patients were included if they were older than the age of 18 years, recruited for study of likely MK, and not concurrently undergoing treatment for other acute eye conditions. For pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…In our study, as well as in the comparable literature, females and males were relatively equally distributed in the overall cohort [ 12 , 15 , 21 , 22 , 26 28 , 38 ]. However, while we found sex-specific differences for Enterobacterales, Pseudomonas, and Staphylococcus aureus , in the other studies, no such difference was identified [ 12 , 15 , 21 , 22 , 26 28 , 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…In our study, as well as in the comparable literature, females and males were relatively equally distributed in the overall cohort [ 12 , 15 , 21 , 22 , 26 28 , 38 ]. However, while we found sex-specific differences for Enterobacterales, Pseudomonas, and Staphylococcus aureus , in the other studies, no such difference was identified [ 12 , 15 , 21 , 22 , 26 28 , 38 ].…”
Section: Discussionsupporting
confidence: 85%
“…A significant proportion of these patients are admitted to hospital to assist in adherence to intensive topical antimicrobial therapy and enable closer monitoring. Cost evaluation of MK in the international literature is lacking with limited studies from the UK, USA, Taiwan and India [ 13 , 14 , 15 , 16 , 17 ]. The mean cost of procedural treatment from 2013–2018 for a patient with MK in the USA was estimated to be USD 1788.7 and in the UK as GBP 2855 (USD 3252) [ 14 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cost evaluation of MK in the international literature is lacking with limited studies from the UK, USA, Taiwan and India [ 13 , 14 , 15 , 16 , 17 ]. The mean cost of procedural treatment from 2013–2018 for a patient with MK in the USA was estimated to be USD 1788.7 and in the UK as GBP 2855 (USD 3252) [ 14 , 16 ]. Due to the differences in healthcare systems and methodologies used, costs reported in previous studies vary widely.…”
Section: Introductionmentioning
confidence: 99%
“…Contact lens-related microbial keratitis (CLMK) is a serious, sight-threatening problem with an estimated rate of two to four per 10 000 contact lens wearers per year [1 ▪ ]. CLMK results in an enormous economic burden due to frequent clinic visits and the cost of medications and procedures [1 ▪ ,2,3]. Contact lenses increase the risk for keratitis by acting as a microbial nidus and breaking down the corneal epithelium to provide an entryway for pathogens.…”
Section: Introductionmentioning
confidence: 99%